(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
The analysis of 56 specimens of the branched, walled post-depositional trace fossil Rutichnus, sampled from 31 thin-bedded, overbank turbidites from the Verghereto Formation, Romagna Apennines, indicates high morphologic variability of this ichnotaxon in hypichnial preservation. The variability concerns the arrangement of outer and inner walls, number and shape of annulations, distribution of pustules, the (false) branching arrangement and the general external shape. Highest variability has been observed mainly in the Rutichnus rutis ichnospecies, clearly less in the R. irregularis ichnospecies that is rare. The Dino-Lite microscope camera analysis of oriented thin sections indicates that endichnial preservation exhibits many structures due to burrowing in soft substrate, destroying laminae of sand. Consequently Rutichnus probably was produced by a worm or arthropod, inducing strong deformation in turbidite sand during the feeding activity on phytodetritus and organic matter transported by the turbidity flow.